Micro and Small Entrepreneur Social Ads: The Influence of Risk Perception as Measured by Self-Monitoring and Social Expectation on Poverty Reduction Social Ads in Indonesia - Afiff, Adi Zakaria (UI Scholars Hub, 2021)
Regardless of the growing usage of social ads in Indonesia, the effectiveness of these social ads has not really been assessed. One theme of the social ads that is related to the poverty problem in this country is the micro and small entrepreneur social ads, namely a number of related social ads issued by the government that persuades its audience to release themselves from poverty by becoming micro and small entrepreneurs that is supported by low cost loans from the government.As becoming a micro or small entrepreneur has both an individual and a social risk perception, a 2x2x2 experiment was conducted using self-monitoring to represent the individual risk perception, social expectation to represent the social risk perception and message framing; to see how these 3 factors affect the target audience attitude toward the message of becoming a micro and small entrepreneur. The result of the study shows that self-monitoring, the individual risk perception, has the strongest influence over the audience’s attitude, in which the higher the self-monitoring characteristic of the audience the more positive the attitude formed toward the message. Social expectation and message framing does not show any direct significant influence, however the interaction of the 2 factors show significant influence toward the attitude the message.